Analisis Sektor Basis dan Tipologi Sektoral Menggunakan Pendekatan Location Quotient dan Tipologi Klassen di Kabupaten Kebumen - Radite Ranggi Ananta; Aura Aulia (Pusat Riset dan Inovasi Nasional, 2024)
Regional economic development is significant in improving the community's standard of living. The success of this development depends on formulating and implementing policies that prioritize sectors with substantial competitive advantages. This research aims to analyze the base and non-base sectors that comprise the economy and the typology of leading sectors to be developed further in Kebumen Regency. The method used in this research is quantitative descriptive to describe the characteristics of Kebumen Regency's economic sectors systematically. The data used is secondary data obtained from the Central Bureau of Statistics (BPS) in the form of Gross Regional Domestic Product (GRDP) data for Kebumen Regency and Central Java Province in 2023. Three analytical tools are used to analyze the leading sectors: Location Quotient (LQ), Dynamic Location Quotient, and Sectoral Klassen Typology. The research results show that five leading sectors in Kebumen Regency are classified as base and prospective sectors, namely (1) Agriculture, Forestry, and Fisheries, (2) Wholesale and Retail Trade, (3) Transportation and Warehousing, (4) Government Administration, Defense, and Mandatory Social Security, and (5) Health Services and Social Activities.